Konflik Perkebunan Kelapa Sawit Antara PT Roempoen Enam Bersaudara dengan Masyarakat Dalam Mendukung Keamanan Wilayah - NUGRAHA, WAHYU (Indonesian Journal Publisher, 2023)
The growing palm oil plantations sector is both given positive and negative impacts. In Addition to being a large contributor to national income and local government revenues, the existence Of palm oil plantation is also being trigger of conflict in community. The root of conflict of palm oil Plantations is mostly related to ownership or control over land and social responsibility that is not Properly implemented by the company. This study aims to analyze the conflict between PT Roempoen Enam Bersaudara with the Community in Sungai Rotan and conflict resolution by stakeholders to solve Problems. Formulation of all arguments, facts and theoretical framework on this research is guided by Descriptive qualitative approach. For data collection techniques, researcher conducts interview, Observation and literature studies. The results show that conflict occurred due to the company Neglected social obligation of the distribution of plasma plantation. Besides there is take over of Company to new management is being trigger conflict rising. Then new management has built big Boundry without socialization to local society first so that the land is displaced. Conflict resolution Have been doing by government of Muara Enim regency through negotiation and mediation between PT Roempoen Enam Bersaudara and local society. Local Government has also formed an integrated Team and land inventory team but the problems of the two parties have not yet resolved. In the end Local government needs to provide the best alternative is more solutive and cooperative so it will Create good relationship between PT Roempoen Enam Bersaudara and society in Sungai Rotan District. With peaceful relations achieved, it will give impact in supporting regional security particulary in Sungai Rotan district.